Pengaruh Status Gizi terhadap Tingkat Kelelahan Pekerja PT. Maruki Internasional Indonesia - Fatmawati Hamid; Salam, Jumhur; Dwiseli, Firmita; Nurgazali, Nurgazali (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Fatigue is a common complaint in the wider community and the working population. Work-related fatigue is a situation where workers experience a decrease in work productivity. This study aims to determine the effect of nutritional status on work fatigue. This type of research is observational analysis with a cross-sectional study design, which is carried out on employees of the production department of PT. Maruki International Indonesia. The research population amounted to 197 people, and 130 people were selected as a sample through the proportional sampling method. Nutritional status data collection is carried out by measuring Body Mass Index (BMI). Work fatigue data was obtained through interviews using a Subjective self-rating test questionnaire from the Industrial Fatigue Research Committee (IFRC). Data analysis was carried out using a linear regression test with SPSS. Based on the results of the study, a p-value of 0.043 (p<0.05) was obtained, so nutritional status had a significant influence on fatigue in employees of the production department of PT. Maruki International Indonesia. So it can be concluded that work fatigue can be influenced by the nutritional status of workers in the Production section of PT. Maruki International Indonesia.